Molecular Chemistry and Engineering of Boron‐Modified Polyorganosilazanes as New Processable and Functional SiBCN Precursors. Issue 38 (2nd May 2017) - Viard, Antoine; Fonblanc, Diane; Schmidt, Marion; Lale, Abhijeet; Salameh, Chrystelle; Soleilhavoup, Anne; Wynn, Mélanie; Champagne, Philippe; Cerneaux, Sophie; Babonneau, Florence; Chollon, Georges; Rossignol, Fabrice; et al.
Abstract: A series of boron‐modified polyorganosilazanes was synthesized from a poly(vinylmethyl‐ co ‐methyl)silazane and controlled amounts of borane dimethyl sulfide. The role of the chemistry behind their synthesis has been studied in detail by using solid‐state NMR spectroscopy, FTIR spectroscopy, and elemental analysis. The intimate relationship between the chemistry and the processability of these polymers is discussed. Polymers with low boron contents displayed appropriate requirements for facile processing in solution, such as impregnation of host carbon materials, which resulted in the design of mesoporous monoliths with a high specific surface area after pyrolysis. Polymers with high boron content are more appropriate for solid‐state processing to design mechanically robust monolith‐type macroporous and dense structures after pyrolysis. Boron acts as a crosslinking element, which offers the possibility to extend the processability of polyorganosilazanes and suppress the distillation of oligomeric fragments in the low‐temperature region of their thermal decomposition (i.e., pyrolysis) at 1000 °C under nitrogen. Polymers with controlled and high ceramic yields were generated. We provide a comprehensive mechanistic study of the two‐step thermal decomposition based on a combination of thermogravimetric experiments coupled with elemental analysis, solid‐state NMR spectroscopy, and FTIR spectroscopy. Selected characterization tools allowed the investigation of specific properties of the monolith‐type SiBCN materials. Abstract : Boron‐based ceramics : Silicoboron carbonitride ceramics have been synthesized from a new generation of boron‐modified polyorganosilazanes as processable and functional precursors (see figure). The role of molecular chemistry and engineering behind the process, including polymer synthesis and pyrolysis, has been investigated. Porous and dense 3D structures have been prepared as proofs of concept.